Pengaruh Online Customer Review, Pengetahuan Produk, dan Kualitas Produk Terhadap Keputusan Pembelian Produk Scarlett Whitenning pada Mahasiswa Universitas Pembangunan Nasional Veteran Jawa Timur - Banis , Achniatuzzahra; Dermawan, Rizky (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of online customer reviews, product knowledge, and product quality on the decision to purchase scarlett whitening products for students at the